Self-determined motivation and state of flow in an extracurricular program of Small Sided Games - Carrasco Beltrán, Hernaldo Julian; Reigal, Rafael E; Fernández Uribe, Sergio; Vallejo Reyes, Felipe; Chirosa Ríos, Luis Javier (Anales de Psicología / Annals of Psychology, 2018)
The aim of this work was to analyze the effects of a Small Sided Games (SSG) extracurricular program based on football in the self-determined motivation and state of flow. The program lasted 11 weeks and 47 adolescents from Playa Ancha (Valparaiso, Chile) (15.57 ± .72 years). A quasi-experimental design pre-post test was used with a control group. In order to evaluate the motivation, the Behavioural Regulation in Exercise Questionnaire (BREQ-3) was used, and, to analyze the flow, the Flow State Scale was used (FSS). The results obtained indicated positive effects of the program on intrinsic regulation, introjected regulation, amotivation, the perception of the challenge-skill balance, the distortion of time and the autotelic experience. These data suggest that sports participation in extracurricular hours could have a positive impact on self-determined motivation and the state of flow, improving the experience of physical-sporting practice in the school context.